25(OH)vitamin D inflammatory and oxidative stress markers in healthy Holstein cows and cows with peri-partum diseases during the transition period - Saba Ahmadi Sheikhsarmast; Ali Afshar Bahrabad; Nima Farzaneh; Mehrdad Mohri (Scientific Reports)
Abstract In dairy cows, the immune system is suppressed around calving, predisposing them to infectious diseases. This study investigated vitamin D levels and various immunological and oxidative stress markers in cows suffering from peri-parturient diseases compared with healthy cows. A total of 45 cows with peri-parturient diseases (including ketosis and uterine diseases) and 23 healthy cows were selected. For statistical comparisons, diseased cows were compared with healthy cows in various ways. To perform statistical comparisons, sick cows were categorized into different stages: first, those with various peri-parturient diseases; second, those with ketosis; and third, those with uterine diseases, for comparison with the healthy groups. Blood samples were collected at three time points: 7 days pre-partum, 7 days post-partum and 21 days postpartum. 25(OH) vitamin D (25(OH) D), interleukins 4 and 10 (IL-4, IL-10), interferon-gamma (INF-γ), immunoglobulin G (IgG), and haptoglobin amounts were measured via ELISA, while total antioxidant capacity (TAC) and malondialdehyde (MDA) amounts were measured spectrophotometrically. The Friedman test revealed significant time effects on 25(OH) D levels in both the healthy and sick groups (p ≤ 0.05). However, no significant differences were detected between healthy and sick cows at any sampling time. IL-4 levels significantly decreased in sick cows during the peri-parturient period, whereas IL-10 levels notably differed only after calving. IgG levels were significantly lower in sick cows than in healthy cows during the first week postpartum. INF-γ levels were significantly lower in sick cows, particularly one week postpartum. Haptoglobin levels were lower in cows with uterine diseases prior to calving. Although time influenced TAC and MDA levels, no significant differences were found between the groups. Overall, these findings indicate that 25(OH) D and certain immunological parameters may play a role in the health status of dairy cows around calving, warranting further investigation into their potential therapeutic effects.